PERTUMBUHAN DAN CARA KERJA DPR-RI PASCA REFORMASI - Yamin, Saefullah; Nurwahyuni, Nurwahyuni (Universitas Wiralodra, 2020)
Post reformation of the role and function of the House of Representatives of Republik Indonesaian (DPR RI) is returned to its corridor as a legislative institution that runs the legislative function (making laws/constitution), besides running budgeting fungction together with the president, and the oversight function of the implementation of the law and the budget in the administration of government carried out by the executive. Related to the lack of productivity of The House of Representatives (DPR) to carry out the legislative function, The performance evaluation of this legislation is not only seen in terms of the quantity of products made but its quality is also an important factor in assessing legislation products. The identification problems in this research are: What is the Position of the House of Representatives in the 1945 Constitution of the State of the Republic of Indonesia, and What is the Process of the Growth of the Post-Reformation House of Representatives. In this research the library research method will be used or library research. Regarding this kind of research it is usually also called